High resolution patterning of PbS quantum dots/graphene photodetectors with high responsivity via photolithography with a top graphene layer to protect surface ligands. Issue 21 (28th September 2021) - Ahn, Seungbae; Chen, Wenjun; Vazquez-Mena, Oscar
Abstract : We use a top-graphene layer to protect QD surface ligands during the lithography process, allowing reliable patterning of hybrid Gr/QD photodetectors via lithography and dry etching. Abstract : Photodetectors based on colloidal quantum dots (CQDs) and single layer graphene (SLG) have shown high responsivity due to the synergy of strong light absorption from CQDs and high mobility from SLG. However, it is still challenging to achieve high-density and small-footprint devices on a chip to meet the demand for their integration into electronic devices. Even though there are numerous approaches to pattern the chemically fragile CQD films, usually they require non-conventional approaches such as stamping and surface modification that may be non-compatible with semiconductor processing. In this study, we show that conventional lithography and dry etching can be used to pattern QD active films by employing a graphene monolayer passivation/protective layer that protects the surface ligands of CQDs. This protective layer avoids damage induced by lithography process solvents that deteriorate the carrier mobility of CQDs and therefore the photoresponse. Herein we report patterning of CQDs using conventional UV photolithography, achieving reproducible five-micron length PbS CQDs/SLG photodetectors with a responsivity of 10 8 A W −1 . We have also fabricated thirty-six PbS CQDs/SLG photodetectors on a single chip to establish micron size photodetectors. This process offers an approach to pattern QDs with conventional UV lithography and dry etching semiconductor technology to facilitate their integration into current semiconductor commercial technology.